2004
DOI: 10.1002/jclp.10262
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐supported cognitive behavioral treatment of anxiety disorders

Abstract: This article reviews the empirical literature pertaining to the use of computer-supported cognitive-behavioral treatment of anxiety disorders, including palmtop computers, virtual reality exposure therapy, and personal computer software programs. The advantages and disadvantages unique to each type of technology are described. The review concludes with a discussion of ethical issues, barriers to the use of technology by clinicians, and suggestions for a process by which scientists and practitioners can concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 57 publications
0
70
0
3
Order By: Relevance
“…16,22,23,25 A successful virtual experience occurs when the users have a sense of presence, defined as a sensation of being inside the virtual environment. [26][27][28][29][30] According to Bellina,22 recent literature has demonstrated that the more immersive the scenario is, the more intense the subsequent emotional state elicited. Specifically, immersive scenarios can increase the sense of presence, or the illusion of ''being there.''…”
Section: Introductionmentioning
confidence: 99%
“…16,22,23,25 A successful virtual experience occurs when the users have a sense of presence, defined as a sensation of being inside the virtual environment. [26][27][28][29][30] According to Bellina,22 recent literature has demonstrated that the more immersive the scenario is, the more intense the subsequent emotional state elicited. Specifically, immersive scenarios can increase the sense of presence, or the illusion of ''being there.''…”
Section: Introductionmentioning
confidence: 99%
“…However, others have suggested that it is not consumers but clinicians who are opposed to the use of technology more broadly in therapy despite lack of empirical evidence of adverse effects on clientÀtherapist relationships (Anderson et al 2004). Although several challenges associated with delivering sessions by telephone were identified by providers, effective strategies were adopted to manage these; for example, having an initial face-to-face session assisted with the development of rapport.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major strengths of this technique is that VR environment provides emerging opportunities to individuals with an active participation in a three-dimensional world. Moreover, participants are able to manipulate their environment via a second position sensor for some environments [29]. In terms of validity as another strength, various research findings suggested that VR environment based performance is predictive of real-world performance.…”
Section: Background and Related Workmentioning
confidence: 99%